Rotary compression process for producing toothed hollow shafts - J. Tomczak (Metalurgija, 2014)
The paper presents the results of numerical analyses of the rotary compression process for hollow stepped shafts with herringbone teeth. The numerical simulations were performed by Finite Element Method (FEM), using commercial software package DEFORM-3D. The results of numerical modelling aimed at determining the effect of billet wall thickness on product shape and the rotary compression process are presented. The distributions of strains, temperatures, damage criterion and force parameters of the process determined in the simulations are given, too. The numerical results obtained confirm the possibility of producing hollow toothed shafts from tube billet by rotary compression methods.